Bovine Mucosal Heparins Are Comparable to Porcine Mucosal Heparin at USP Potency Adjusted Levels - Jeske, Walter; Kouta, Ahmed; Farooqui, Ambar; Siddiqui, Fakiha; Rangnekar, Varun; Niverthi, Manoj; Laddu, Rajan; Hoppensteadt, Debra; Iqbal, Omer; Walenga, Jeanine; Fareed, Jawed (Frontiers in Medicine, 2019)
Introduction: Bovine mucosal heparins (BMH) are currently being developed for re-introduction for both medical and surgical indications. BMH active pharmaceutical ingredient (API) exhibits a somewhat weaker USP potency when compared to PMHs. We hypothesized that when dosages are normalized based on the USP reference heparin, BMH will exhibit comparable in vitro and in vivo effects to those produced by PMH. Therefore, studies were developed to compare the APIs of the bovine and the PMH. Materials and Methods: API versions of PMH were obtained from Celsus Laboratories (Franklin, OH). API versions of BMH were obtained from Kin Master (Passo Fundo, Brazil). Each of these heparins was assayed for their molecular weight profile, AT affinity, USP potency and anticoagulant/antiprotease profiles using standard laboratory methods. In vitro protamine neutralization studies were carried out. Molecular weight profile and other physicochemical properties were also measured. Antithrombotic and hemorrhagic effects were measured in rats and pharmacodynamic profiles were assessed in primates. Results. PMH and BMH exhibited comparable molecular weight profiles as determined by size exclusion chromatography (BMH: 21.6 ± 1.0 kDa and PMH: 18.9 ± 0.6 kDa). BMH exhibited a potency of 140 U/mg while PMH had a potency of 195 U/mg. In the anticoagulant and antiprotease assays, the BMH exhibited lower functionality which was proportional to USP potency. When the BMH was compared with PMH at potency adjusted concentrations, it showed identical calibration curves in the aPTT and anti-protease assays. However, in the protamine neutralization studies, BMH required slightly higher amounts of protamine in contrast to PMH. BMH and PMH administered to rats at equivalent anti-Xa dosages resulted in comparable antithrombotic activity and prolongation of bleeding time. Similar pharmacodynamic profiles were observed in primates when BMH and PMH were dosed on an anti-Xa U/kg basis. Conclusion: BMH at adjusted biologic potency is comparable to PMH, however, it requires proportionally higher amount of protamine due to the increased mass for adjusting to higher potency. Additional studies on the structural characterization, interactions with PF4 and in vivo neutralization studies are being carried out.